2020
DOI: 10.1128/jvi.02169-19
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Influenza A Viruses in Japanese Swine in 2015 to 2019

Abstract: To assess the current status of influenza A viruses of swine (IAVs-S) throughout Japan and to investigate how these viruses persisted and evolve on pig farms, we genetically characterized IAVs-S isolated during 2015 to 2019. Nasal swab samples collected through active surveillance and lung tissue samples collected for diagnosis yielded 424 IAVs-S, comprising 78 H1N1, 331 H1N2, and 15 H3N2 viruses, from farms in 21 sampled prefectures in Japan. Phylogenetic analyses of surface genes revealed that the 1A.1 class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Our serological investigation revealed the high seroprevalence of H1 IAV infection in pigs in 2011. The positive rate and neutralization titres for A(H1N1)pdm09 virus were higher than those for the moto et al, 2012;Mine et al, 2020;Ozawa et al, 2015). Since both A(H1N1)pdm09 and human H3N2 viruses were isolated from pigs in Zambia, it might be possible for such a reassortant IAV to emerge in pigs in Zambia.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our serological investigation revealed the high seroprevalence of H1 IAV infection in pigs in 2011. The positive rate and neutralization titres for A(H1N1)pdm09 virus were higher than those for the moto et al, 2012;Mine et al, 2020;Ozawa et al, 2015). Since both A(H1N1)pdm09 and human H3N2 viruses were isolated from pigs in Zambia, it might be possible for such a reassortant IAV to emerge in pigs in Zambia.…”
Section: Discussionmentioning
confidence: 87%
“…Although human seasonal influenza H3N2 viruses were also isolated from pigs in Japan, no descendant strains were subsequently isolated, suggesting that these viruses were sporadically introduced into pigs from humans without establishment of novel IAV lineages (Takemae et al., 2013). On the other hand, H3N2 IAV variants recently generated by the reassortment between A(H1N1)pdm09 and human seasonal H3N2 viruses might be well adapted to swine and have established a novel IAV lineage in pig populations in Asia, including Japan and Thailand (Hiromoto et al., 2012; Mine et al., 2020; Ozawa et al., 2015). Since both A(H1N1)pdm09 and human H3N2 viruses were isolated from pigs in Zambia, it might be possible for such a reassortant IAV to emerge in pigs in Zambia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1), indicating the N2 genes of swine in uenza A viruses in different regions were introduced from human in uenza A viruses at different time points. After the 2009 pandemic, the gene segments of A(H1N1)pdm09 were reintroduced into the swine population, resulting in the circulation of different genotypes in the swine population [8][9][10][11][12]. Humans infected by reassortant swine in uenza viruses with the gene pool of A(H1N1)pdm09 virus have been sporadically detected [13,14,16,23], and it has been reported that Eurasian avian-like swine in uenza A(H1N1) virus with A(H1N1)pdm09 genes has facilitated human infection [24].…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, with multiple introductions of human and avian in uenza A viruses into the swine population in different time periods, multiple genotypes and clades of A(H1) and A(H3) viruses have been generated through inter-and intra-subtype reassortment [7]. Later, upon the 2009 pandemic, the viral gene pools of human in uenza A(H1N1)pdm09 viruses were reintroduced into the swine population through reassortment, resulting in the circulation of different genotypes in swine and increasing the threat of the next pandemic [8][9][10][11][12]. Human infections caused by in uenza A(H1)v and A(H3)v viruses with the matrix protein from A(H1N1)pdm09 have been sporadically reported [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%